Technopreneurship For Local Economic Empowerment by Innovative Learning Module - Herwin Mopangga; Frahmawati Bumulo (Journal of International Conference Proceedings (JICP), 2018)
This research aims to explain the students understanding and mastery of economics and development of technopreneurship-based economics learning module. Qualitative and descriptive approaches were applied for the research which was begun by some observations and Economics and Entrepreneurship learning identification in 15 study programs of diploma and bachelor degree at State University of Gorontalo or UNG. The data was gathered in the forms of documentation, literature studies, and questionnaires purposively distributed to 100 students. The results showed that: 1) Students realized the importance of learning, understanding, and analyzing the development of Economics not only for academic purpose yet for creating new jobs in society; 2) Economics learning results in UNG at academic year 2014/2015 showed satisfying results based on compared achievement percentage of score A, B, and C at 36%, 50%, and 14% respectively; and 3) In order to have more interesting and well-targetted learning, the contextual and applicable Economics learning module needed to be redesigned. That module would facilitate students in understanding the social reality, such as the increment of intellectual unemployment and the importance of creating more innovative entrepreneurship activities. Keywords: module, Economics, technopreneurship.